2023
DOI: 10.1002/adhm.202300469
|View full text |Cite
|
Sign up to set email alerts
|

Dual Photo‐Enhanced Interpenetrating Network Hydrogel with Biophysical and Biochemical Signals for Infected Bone Defect Healing

Abstract: The healing of infected bone defects (IBD) is a complex physiological process involving a series of spatially and temporally overlapping events, including pathogen clearance, immunological modulation, vascularization, and osteogenesis. Based on the theory that bone healing is regulated by both biochemical and biophysical signals, in this study, a copper doped bioglass (CuBGs)/methacryloyl‐modified gelatin nanoparticle (MA‐GNPs)/methacrylated silk fibroin (SilMA) hybrid hydrogel is developed to promote IBD heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…In another study, Xu et al found that copper decreased macrophage pro-inflammatory gene expression and increased anti-inflammatory gene expression 73 . While Jian et al found that copper-containing hydrogel-treated macrophages exhibited more M1 polarization on day 3 and more M2 polarization on day 7 74 . This inconsistency may be due to the fact that the regulation of macrophage polarization by copper ions is concentration-dependent, as a recent in vitro study found that treatment of the THP-1 monocyte cell line with Cu 2+ at concentrations lower than 10 μM for 48 h promoted the expression of M2 macrophage-associated markers, whereas Cu 2+ at concentrations higher than 100 μM increased M1 macrophage-associated marker expression 75 .…”
Section: Copper and Wound Healingmentioning
confidence: 94%
“…In another study, Xu et al found that copper decreased macrophage pro-inflammatory gene expression and increased anti-inflammatory gene expression 73 . While Jian et al found that copper-containing hydrogel-treated macrophages exhibited more M1 polarization on day 3 and more M2 polarization on day 7 74 . This inconsistency may be due to the fact that the regulation of macrophage polarization by copper ions is concentration-dependent, as a recent in vitro study found that treatment of the THP-1 monocyte cell line with Cu 2+ at concentrations lower than 10 μM for 48 h promoted the expression of M2 macrophage-associated markers, whereas Cu 2+ at concentrations higher than 100 μM increased M1 macrophage-associated marker expression 75 .…”
Section: Copper and Wound Healingmentioning
confidence: 94%
“…78 Light curing is a commonly used strategy for enhancing cohesion, mainly manifested in the enhancement of the mechanical strength of hydrogels, to prevent hydrogels from breaking under the effect of peeling forces, resulting in adhesive failure. 79,80 Qian et al proposed a novel hybrid hydrogel based on glycyrrhizic acid (GA). This hybrid hydrogel is composed of an interpenetrating polymer network with Zn 2+ -induced GA self-assembly as the primary network and photocrosslinked methyl acrylated silk fibroin as the secondary network (Fig.…”
Section: Smart Hydrogels For Wound Bandagingmentioning
confidence: 99%